2013
DOI: 10.1155/2013/976032
|View full text |Cite
|
Sign up to set email alerts
|

Green Chemical Synthesis and Analgesic Activity of Fluorinated Thiazolidinone, Pyrazolidinone, and Dioxanedione Derivatives

Abstract: Facile lemon juice catalyzed green and efficient synthesis of a series of new classes of 5-(fluorinatedbenzylidene)-2-thioxo-1,3-thiazolidin-4-ones (3a–e), 5-methyl-4-(fluorinatedbenzylidene)-2-phenylpyrazolidin-3-ones (5a–e), and 2,2-dimethyl-5-(fluorinatedbenzylidene)-1,3-dioxane-4,6-diones (7a–e) by the reaction of fluorinated aromatic aldehydes with active methylene compounds is reported. Lemon juice is natural acid catalyst which is readily available, cheap, nontoxic, and ecofriendly. This method is exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…Thiazoles are another important members of azole family known for their various biological properties such as antioxidant 5 , antimicrobial [6][7][8] , anticancer 9 and analgesic 10 etc. More recently it has been shown that thiazole containing pyrazoles have proved their potential as antimicrobial 11,12 agents.…”
Section: Oriental Journal Of Chemistrymentioning
confidence: 99%
“…Thiazoles are another important members of azole family known for their various biological properties such as antioxidant 5 , antimicrobial [6][7][8] , anticancer 9 and analgesic 10 etc. More recently it has been shown that thiazole containing pyrazoles have proved their potential as antimicrobial 11,12 agents.…”
Section: Oriental Journal Of Chemistrymentioning
confidence: 99%
“…1 The N,N-heterocycle compounds are also key building blocks in chemical synthesis and component in many pharmaceutical agents possessing unique bioactivities. 2 Consequently, the realisation of efficient methods for their preparation and modification continues to be an actively pursued area of organic chemistry. 1–8…”
Section: Introductionmentioning
confidence: 99%
“…2 Consequently, the realisation of efficient methods for their preparation and modification continues to be an actively pursued area of organic chemistry. 1–8…”
Section: Introductionmentioning
confidence: 99%
“…The pyrazolidinone (pyrazolidin-3-one) moiety is an important structural motif that can be found both in natural products and in synthetic compounds with interesting pharmacological activity (analgesic, antibiotic, anticonvulsant, and with inhibitory cyclooxygenase, lipoxygenase, and γ-aminobutyrate transferase activity, among others) [1,2,3,4,5,6,7,8,9,10]. On the other hand, the selective oxidation of pyrazolidinones affords the corresponding pyrazolones (pyrazol-5-ones), a class of compounds that also exhibits very relevant pharmacological properties [11,12,13,14,15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%